Cellular and Biochemical Mechanisms of the Retroviral Restriction Factor SAMHD1. (17th July 2013) - Wu, Li
Abstract : Replication of HIV-1 and other retroviruses is dependent on numerous host proteins in the cells. Some of the host proteins, however, function as restriction factors to block retroviral infection of target cells. The host protein SAMHD1 has been identified as the first mammalian deoxynucleoside triphosphate triphosphohydrolase (dNTPase), which blocks the infection of HIV-1 and other retroviruses in non-cycling immune cells. SAMHD1 protein is highly expressed in human myeloid-lineage cells and CD4 + T-lymphocytes, but its retroviral restriction function is only observed in noncycling cells. Recent studies have revealed biochemical mechanisms of SAMHD1-mediated retroviral restriction. In this review, the latest progress on SAMHD1 research is summarized and the mechanisms by which SAMHD1 mediates retroviral restriction are analyzed. Although the physiological function of SAMHD1 is largely unknown, this review provides perspectives about the role of endogenous SAMHD1 protein in maintaining normal cellular function, such as nucleic acid metabolism and the proliferation of cells.